Qing-Luo-Yin Alleviated Monocytes/Macrophages-Mediated Inflammation in Rats with Adjuvant-Induced Arthritis by Disrupting Their Interaction with (Pre)-Adipocytes Through PPAR-γ Signaling - Wang R; Li DF; Hu YF; Liao Q; Jiang TT; Olatunji OJ; Yang K; Zuo J (Dove Medical Press, 2021)
Rui Wang,1,2,* Dan-Feng Li,1,2,* Yi-Fang Hu,1,2 Qiang Liao,1,2 Tian-Tian Jiang,1,2 Opeyemi Joshua Olatunji,3 Kui Yang,2,4 Jian Zuo1,2,5 1Department of Traditional Chinese Medicine, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People's Republic of China; 2Research Center of Integration of Traditional Chinese and Western Medicine, Wannan Medical College, Wuhu, 241000, People's Republic of China; 3Faculty of Traditional Thai Medicine, Prince of Songkla University, Hat Yai, 90112, Thailand; 4Department of Pharmacy, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People's Republic of China; 5Key Laboratory of Non-coding RNA Transformation Research of Anhui Higher Education Institution, Wannan Medical College, Wuhu, 241000, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian ZuoDepartment of Traditional Chinese Medicine, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People's Republic of ChinaEmail zuojian8178@163.comBackground: The Chinese herbal formula Qing-Luo-Yin (QLY) has been successfully used in rheumatoid arthritis treatment for decades. It exhibits notable immune and metabolism regulatory properties. Thereby, we investigated its effects on the interplay between (pre)-adipocytes and monocytes/macrophages under adjuvant-induced arthritis (AIA) circumstances.Methods: Fat reservoir and histological characteristics of white fat tissues (WAT) in AIA rats receiving QLY treatment were examined upon sacrifice. Metabolic parameters, clinical indicators, and oxidative stress levels were determined using corresponding kits, while mRNA/protein expression was investigated by PCR and immunoblotting methods. M1 macrophage distribution in WAT was assessed by flow cytometry. The effects of QLY on (pre)-adipocytes were further validated by experiments in vitro.Results: Compared with normal healthy controls, body weight and circulating triglyceride were declined in AIA rats, but serological levels of free fatty acids and low-density lipoprotein cholesterol were increased. mRNA IL-1β and iNOS expression in white blood cells and rheumatoid factor, C-reactive protein, anti-cyclic citrullinated peptide antibody, MCP-1 and IL-1β production in serum/WAT were up-regulated. Obvious CD86+CD11b+ macrophages were enriched in WAT. Meanwhile, expression of PPAR-γ and SIRT1 and secretion of adiponectin and leptin in these AIA rats were impaired. QLY restored all these pathological changes. Of note, it significantly stimulated PPAR-γ expression in the treated AIA rats. Accordingly, QLY-containing serum promoted SCD-1, PPAR-γ, and SIRT1 expression in pre-adipocytes cultured in vitro. AIA rats-derived peripheral blood mononuclear cells suppressed PPAR-γ and SCD-1 expression in co-cultured pre-adipocytes, but serum from AIA rats receiving QLY treatment did not exhibit this potential. The changes on PPAR-γ expression eventually resulted in varied adipocyte differentiation statuses. PPAR-γ selective inhibitor T0070907 abrogated QLY-induced MCP-1 production decline in LPS-primed pre-adipocytes and reduced adiponectin secretion.Conclusion: QLY was potent in promoting PPAR-γ expression and consequently disrupted inflammatory feedback in WAT by altering monocytes/macrophages polarization and adipocytes differentiation.Keywords: fat metabolism, Qing-Luo-Yin, rheumatoid arthritis, macrophages polarization, adipokine, (pre)-adipocytes